A Comparative Study of Conductance of Sodium Dodecyle Sulphate (SDS) in Different Percentage of Ethanol Water Mixed Solvent Media at 298.15 K Temperature - Yadav, Chandradip Kuma (NUTA Journal, 2018)
Precise measurement of the conductivity of sodium dodecyl sulphate in different percentage of (0%, 10%, 20%) ethanol-water mixed solvent media containing at 298.15 K temperature were measured. The specific conductivities exhibit a sharp increase with increase in concentration with in the concentration range investigated (0.001 to 0.020) mol per liter. The increase in the conductance with concentration is due to an increase in the number of ion per unit volume of the solution. But decrease in conductance with increase in percentage of ethanol - water mixed solvent media at particular temperature 298.15 K. Ionizing effect is decrease with increase in percentage of ethanol - water mixed solvent media at 298.15K. Due to decrease in dielectric constant with increase in percentage of ethanol - water mixed solvent media at particular temperature 298.15 K. conductivity order is 0% > 10% > 20% at particular temperature 298.15 K.